Evaluation of the SLOMYCO Sensititre® panel for testing the antimicrobial susceptibility of Mycobacterium marinum isolates. Issue 1 (December 2016) - Chazel, Marion; Marchandin, Hélène; Keck, Nicolas; Terru, Dominique; Carrière, Christian; Ponsoda, Michael; Jacomo, Véronique; Panteix, Gilles; Bouzinbi, Nicolas; Bañuls, Anne-Laure; Choisy, Marc; Solassol, Jérôme; et al.
Abstract Background The agar dilution method is currently considered as the reference method forMycobacterium marinum drug susceptibility testing (DST). As it is time-consuming, alternative methods, such as the E-test, were evaluated forM. marinum DST, but without success. The SLOMYCO Sensititre® panel, recently commercialized by TREK Diagnostic Systems (Cleveland, OH), can be used for DST in slow-growing mycobacteria and for antimicrobial agents recommended by the Clinical and Laboratory Standards Institute (CLSI) forM. marinum DST. The main goal of this work was to evaluate the SLOMYCO Sensititre® panel method for DST inM. marinum isolates from human patients and fish relative to the reference agar dilution method. Methods/Results The reproducibility of the minimum inhibitory concentration (MIC) determination (±1 log2 dilution) was very good for both the agar dilution method and SLOMYCO Sensititre® panel (>90 % agreement). The percentage essential agreement between methods varied, depending on the drug: between 97 and 75 % for ciprofloxacin, moxifloxacin, linezolid, isoniazid, clarithromycin, amikacin, rifabutin and rifampin, 74 % for trimethoprim, 72 % for doxycycline, 70 % for sulfamethoxazole, 59 % for streptomycin, 33 % for ethambutol and only 2.2 % for ethionamide. When the agar dilution and SLOMYCO Sensititre® panel results were converted into interpretive criteria, the category agreement was 100 % for amikacin, ciprofloxacin, clarithromycin, moxifloxacin, rifabutin, sulfamethoxazole and trimethoprim, 98 % for ethambutol and 96 % for rifampin and no agreement for doxycycline. Conclusions The SLOMYCO Sensititre® panel method could provide a potential alternative to the reference agar dilution method, when DST inM. marinum is required, except for doxycycline.